Study of novel metal complexes derived from a flexible polydentate ligand for biological and biomedical applications - Londoño-Mosquera, Juan-David; Polo, Dorian (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This work shows the synthesis of four new lanthanide complexes of Gd(III), Eu(III), Dy(III) and Yb(III) ions, using two polydentate ligands F and L in order to evaluate their potential application on the contrast-imaging by fluorescent microscopy (MF), nuclear magnetic resonance (RMI) and as antibacterial agents. We propose a structure where both ligands are bound to the metal centre through –OH, -N- and –COO- groups, exhibiting an apparent coordination number of 7. Moreover, r1 molar relaxivities obtained demonstrates that all the complexes had the capability to accelerate longitudinal relaxation times (T1) of water, with a r1 value of 6.45 mmol-1·L-1·s-1 for compound 1, which was higher than r1 of 2.25 mmol-1·L-1·s-1 corresponding to commercial drug Dotarem® employed for RMI. Furthermore, all quantum yields of fluorescence, in reference to fluorescein, where lower than 1%, showing a poor performance in emission processes of visible radiation. Stability constants determined as (-log[kap]) were between 21 and 18, being even better than some contrast agents. Finally, DNA binding experiments showed that all complexes had the capability to bind DNA strands by a possible intercalation mechanism.